Guidance on safety evaluation of sources of nutrients and bioavailability of nutrient from the sources (Revision 1). (27th March 2021) - ,; Younes, Maged; Aggett, Peter; Aguilar, Fernando; Crebelli, Riccardo; Dusemund, Birgit; Filipič, Metka; Frutos, Maria Jose; Galtier, Pierre; Gundert‐Remy, Ursula; Kuhnle, Gunter Georg; Lambré, Claude; et al.
Abstract: Endorsement date 21 January 2021 Implementation date 27 March 2021 This guidance describes the scientific data required to allow an evaluation of the safety of new substances that are proposed for use as sources of nutrients in food supplements, foods for the general population or foods for specific groups and an assessment of the bioavailability of the nutrient from the proposed source. This guidance describes the scientific data required to allow an evaluation of the safety of the source within the established framework for risk assessment of food additives and novel food ingredients and the bioavailability of the nutrient from this source. This document is arranged in five main sections: one on technical data aimed at characterising the proposed source and at identifying potential hazards resulting from its manufacture and stability in food; one on existing authorisations and evaluation, providing an overview of previous assessments on the proposed source and their conclusions; one on proposed uses and exposure assessment section, allowing an estimate of the dietary exposure to the source and the nutrient based on the proposed uses and use levels; one on toxicological data, describing approaches which can be used to identify (in conjunction with data on manufacture and composition) and to characterise hazards of the source and any relevant breakdown products; the final section on bioavailability focuses on determining the extent to which the nutrient from the proposed source is available for use by the body in comparison with one or more forms of the same nutrient that are already permitted for use on the positive lists. This guidance was adopted by the Panel on Food Additives and Nutrient Sources added to Food (ANS Panel) on 16 May 2018. Upon request from EFSA, the present guidance has been revised to inform applicants of new provisions set out in Regulation (EC) No 178/2002, as amended by Regulation (EU) 2019/1381 on the transparency and sustainability of the EU risk assessment in the food chain.